Концепция непрерывного образования и состояние неразрывности содержания обучения в системе непрерывного профессионального образования «ПК-ВУЗ» - Мусаева, Н.Н. (SCIENCE and SOCIETY, 2018)
In the article the concepts of continuous education have been analyzed. It is justified that the development of concepts is carried out in the direction of establishing closer ties with life, the transition from theoretical education to practical education involving the acquisition of skills that meet the modern demand of society. The necessity of synthesis of the principles of the organization of contin- uous education with the identification of the characteristics of the continuity of education is determined.
Keywords: continuous education; the concept of continuous education; continuity